Peningkatan Keterampilan Interaksi Sosial Guru Pendidikan Agama Kristen dalam Proses Pembelajaran - Dorlan Naibaho; Rani Apriana Purba (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
Social skills in the importance of Christian Religious Education (PAK) teacher professionalism in developing creativity in learning. Religious Education teachers who lack creativity can lead to failure in creating inspiring learning. This can have a negative impact on exam results and student character development. John M. Nainggolan emphasized that a Christian teacher must put others first, have a work ethic, and contribute to meeting students' needs. Creativity is an important aspect in meeting students' needs in achieving achievement and application in everyday life.Time limitations often become an obstacle to the creativity of PAK teachers. However, from the perspective of Christian education, an educator is responsible for developing all students' potential so that they can develop optimally affectively, cognitively and psychomotorically. Teachers have an important role in shaping personality, creativity, as well as providing motivation and guidance to students.Christian religious education also requires creativity from PAK teachers in conveying religious messages so that students can understand and appreciate them. Jesus' activities as a teacher became a model for Christian teachers to continue implementing the educational revolution in teaching approaches.The skills of explaining, social, asking questions, providing reinforcement, varying stimuli, as well as the ability to open and close learning are important aspects of the basic skills of a PAK teacher. Learning success is not only determined by well-formulated objectives, but also by appropriate teaching methods.Apart from that, PAK teachers are also expected to have personal characteristics such as culture, competence, principles of the Christian faith, determination, responsibility, humor and imagination that support professionalism in conveying Christian religious messages and supporting students directly. Effective communication between teachers and students becomes key in ensuring messages are distributed well. The support and guidance provided by teachers is also an important factor in the school environment, where teachers become important resources for students outside the home environment.In conclusion, the professionalism of PAK teachers is not only limited to knowledge of Christianity, but also includes creativity, basic teaching skills, and effective communication to help students achieve achievement and develop character.